2002
DOI: 10.1007/s00248-002-2003-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Phenol-Degrading Bacteria Isolated from Different Egyptian Ecosystems

Abstract: Twelve selected phenol-degrading bacterial isolates were obtained on phenol agar plates using culture enrichment technique. Molecular identification of the isolates was performed using eubacterial 16S rRNA PCR specific primers. Based on 16S rDNA sequence analysis, the results revealed that the majority of the isolates (8 out of 12) are affiliated to the g-subdivision of Proteobacteria. Four out of the eight isolates are closely related to the genus Acinetobacter. Molecular heterogeneity among the phenol-degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Members of the genus Acinetobacter are usually isolated in water. They are capable of degrading aromatic compounds and their metabolic versatility is comparable to that of the Pseudomonads (Abd-El-Haleen et al, 2002). Chromobacterium is ubiquitous in nature and found in waters from polar regions to the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Acinetobacter are usually isolated in water. They are capable of degrading aromatic compounds and their metabolic versatility is comparable to that of the Pseudomonads (Abd-El-Haleen et al, 2002). Chromobacterium is ubiquitous in nature and found in waters from polar regions to the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on phenol toxicity to bacteria have shown that bacteria can adapt a low level of phenol concentrations, but increasing phenol concentrations appeared to decrease overall phenol degradation (Dean and Rahimi, 1995). A range of phenol-degrading microorganisms have been identified, including Acinetobacter (Abd et al, 2002), Bacillus (Arutchelvan et al, 2005), Burkholderia (El et al, 2003), Pseudomonas (Whiteley et al, 2001), Valivorax (Watanabe et al, 1998), mesophilic and thermophilic methanogens , and the yeast Candida tropicalis (Jiang et al, 2005). Many studies proved that phenol-degrading bacteria have been isolated from natural soils (De et al, 2005), plants roots (Wang et al, 2007), root nodules (Wei et al, 2008), rivers (Parvanov and Topalova, 2008), and marine ecosystems (Shashirekha et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated phenols are common environmental contaminants; they have been extensively used as biocides, mainly as wood preservatives (Abd-El-Haleem et al, 2002). Chlorinated phenols and other chlorinated phenollic compounds are also formed as by-products when chlorine is used for bleaching of pulp (Kringstad and Lindstrom, 1984) and for disinfection of drinking water and waste water containing phenols (Ahlborg and Thunberg, 1980;Detrick, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In general, biological methods are preferable methods to treat aromatic compounds because it is economical, and there is a low possibility of the production of byproducts (Marcos et al, 1997). In this concern, several microorganisms used are usually aerobes, including Acinetobacter (Abd-El-Haleem et al, 2002), Pseudo-monas putida ( Tarık and Ermine, 2004), Ochromonas sp. (Semple and Cain, 1996), and Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%